Cement-ash compositions with ash - fluidized bead removal - Akhmednabiev, Rasul; Yalovehin, Andrii (Academic journal Industrial Machine Building Civil Engineering, 2025)
The results of studies of ash-fluidized bed removal by X-ray structural analysis, differential thermal analysis and IR spectrometry are presented. Ashes and ash-slags of the fluidized bed have slightly different properties due to the fact that in fluidized bed boilers the fuel is burned for several seconds longer than in traditional boilers. During this time, the dispersed part of the mineral component of the fuel has time to melt and transform into a glass phase, as a result of which their internal energy increases and they become capable of chemical reactions. The results of the research allowed us to establish that the fly ash of anthracene coal from domestic deposits when burned in a fluidized bed can be classified as medium-calcium and sulfate, which may hide the manifestation of hydration properties. The results of the IR spectrometry study confirmed the presence of calcium sulfate compounds of the gypsum and anhydride type in the fly ash composition. Sulfate minerals in the presence of aluminates and moisture can contribute to the formation of the ettringite mineral during the hardening of cement-ash compositions, which can contribute to the emergence of expansion stresses in cement stone. However, the study of cement-ash stone by X-ray structural analysis methods at the age of six months does not confirm the formation of ettringite. Testing of cement-ash compositions showed that the strength of the compositions at the vintage age is somewhat lower than that of cement stone. However, with a further increase in the hardening period, the rate of strength gain of the compositions is somewhat greater than that of cement stone.